The Construction of Cultural Identity in Digital Communication: A Netnographic Study of Facebook Pro Creators in Enrekang in Building Engagement - Nurjannah D; Jeanny Maria Fatimah; Muhammad Farid (Program Studi Ilmu Komunikasi Universitas Serang Raya, 2026)
This study aims to analyze the construction of cultural identity in the digital space through the communication strategies employed by Facebook Pro creators from Enrekang to build audience engagement. This study uses a qualitative approach with the netnography method to understand communication practices, cultural representations, and social interactions occurring in digital media. Research data was obtained through observation of Facebook Pro creators’ content, interactions in the comment section, digital documentation, and analysis of communication activities occurring on the Facebook Pro platform. The results indicate that Facebook Pro creators in Enrekang construct cultural identity through the use of local language, regional humor, and representations of daily life. These local cultural elements are utilized as communication strategies to foster emotional closeness with the audience. Creators also employ interactive communication through active responses in the comment section, thereby building closer social relationships with the audience. On the other hand, the audience plays a role in reinforcing cultural identity through the use of the local language, providing comments, and participating in digital interactions. Social media is not only a means of communication and entertainment but also a space for the representation of local culture and the formation of social identity in the digital age.